Statistical Analysis of Structural Change of Registered Unemployment in Ukraine - Khobta, M. O.; Sukmanіuk, V. M.; Selivanova, S. V. (Statistics of Ukraine, 2025)
The article examines structural characteristics of registered unemployment in Ukraine in 2021–2024 in conditions of socio-economic instability and martial law. The relevance of the study is due to the need to assess changes in the labor market during a period of deep transformations caused by full-scale armed aggression, migration processes, relocation of enterprises and changes in the employment structure of the population. The purpose of the article is to conduct a statistical analysis of the dynamics of registered unemployment, as well as identify the main trends and factors affecting its change in the period under study.The methodological basis of the study is general scientific and special statistical methods, in particular the analysis of absolute and relative indicators, time series methods, structural and comparative analysis. The information base was official data from state bodies on the number of registered unemployed and demographic indicators.The analysis revealed a steady trend towards a reduction in the number of registered unemployed in 2021–2024, with the most intense decrease in 2021–2023. Significant structural shifts in the composition of the unemployed population by gender, age, level of education and reasons for job loss were identified, in particular, an increase in the share of women and middle-aged people among the registered unemployed. It is substantiated that the decrease in official unemployment rates does not reflect the real scale of the problem and is largely due to administrative, migration and institutional factors.The conclusion is made about the need for a comprehensive approach to assessing unemployment, taking into account hidden forms of unemployment and increasing the effectiveness of state employment policy in the context of post-war economic recovery. The practical value of the study lies in the possibility of using its results by state authorities and local governments in developing active employment policy programs, forecasting labor market needs, and substantiating strategic decisions in the field of socio-economic development of Ukraine.